2020
DOI: 10.1007/s00259-020-04974-w
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic lymph-node staging with 18F-DCFPyL PET/CT prior to extended pelvic lymph-node dissection in primary prostate cancer - the SALT trial -

Abstract: Purpose The detection of lymph-node metastases (N1) with conventional imaging such as magnetic resonance imaging (MRI) and computed tomography (CT) is inadequate for primarily diagnosed prostate cancer (PCa). Prostate-specific membrane antigen (PSMA) PET/CT is successfully introduced for the staging of (biochemically) recurrent PCa. Besides the frequently used 68 gallium-labelled PSMA tracers, 18 fluorine-labelled PSMA tracers are available. This study examined the diagnostic accuracy of 18 F-DCFPyL (PSMA) PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 33 publications
(70 reference statements)
2
53
0
1
Order By: Relevance
“…Many prospective studies that have used histopathology as a validation have already demonstrated adequate diagnostic performance of PSMA PET/CT in primary nodal staging [12,13,[17][18][19]. However, only a small number of prospective multimodality comparative studies are available [20][21][22], and none conducted using 18 F-PSMA-1007 tracer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many prospective studies that have used histopathology as a validation have already demonstrated adequate diagnostic performance of PSMA PET/CT in primary nodal staging [12,13,[17][18][19]. However, only a small number of prospective multimodality comparative studies are available [20][21][22], and none conducted using 18 F-PSMA-1007 tracer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a limited number of studies evaluating 18 Flabelled PSMA tracers in the detection of PCa regional lymph node metastases have been published [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…After histopathologic confirmation, the node-based sensitivity and PPV of 18 F-DCFPyL were 31-42% and 78-91%, respectively (21). Comparable node-and patient-based sensitivities of 34.7% and 41.2% were observed in another trial of 18 F-DCFPyL PET/CT in patients with intermediate-to-high-risk PC undergoing RP with PLND (the SALT trial) (22). Finally, 68 Ga-PSMA-11 PET imaging was directly compared to conventional imaging in a large multicenter randomized clinical trial of 302 men with newly diagnosed high-risk PC (ProPSMA).…”
Section: Methodsmentioning
confidence: 94%
“…68 Ga-PSMA-11 PET/CT significantly outperformed conventional imaging, with diagnostic accuracies of 92% and 65%, sensitivities of 85% and 38%, and specificities of 98% and 91%, respectively (23). Importantly, selection for a higher risk population and lack of a confirmatory pelvic nodal dissection in most cases may have contributed to the higher sensitivity and PPV observed in ProPSMA compared to other studies of PSMA-based imaging in patients with clinically localized PC (20)(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…The treatment plan was adjusted after 18 F-DCFPyL in 17% (n = 27) of the patients. Jansen et al [53] prospectively analyzed 117 patients who underwent imaging prior to robot-assisted radical prostatectomy and extended pelvic lymph node dissection, in order to determine the diagnostic accuracy of 18 F-DCFPyL PET/CT for pelvic lymph node staging in intermediate-(36.8%) and high-risk (63.3%) PCa. Histological lymph node metastases were found in 17/117 (14.5%) patients, of whom seven had a suspicious PET/CT, resulting in a limited sensitivity (41.2%), but high specificity (94.0%).…”
Section: Modern Nuclear Imaging In Prostate Cancer: New Pet/ct Radiotracersmentioning
confidence: 99%